The rise of the rustbelt - Cooke, Philip (Philip N.) (London : UCL Press, 1995)
The Rise of the Rustbelt demonstrates the value of interchange and comparison of ideas and policies for industrial regeneration between three major regions: the Great Lakes of North America, the Ruhrgebiet of North-Rhine-Westphalia, and the industrial belt of South Wales. The top priority of these areas is to conserve and retain their status as industrial powerhouses by attracting investment to compensate for their dramatic structural decline over the past twenty years and more. They have much to learn from one another. Encompassing environmental and sociocultural issues, as well as those of i.
11 The dash for gas â€? consequences and opportunities12 Restructuring policies -- 13 Keeping to the high road -- References -- Index
Includes bibliographical references (pages 247-258) and index.
English.
Print version record.
eBooks on EBSCOhost
Keywords: Industries -- Great Lakes Region (North America); Industries -- Germany -- Ruhr (Region); Industries -- Wales, South; Steel industry and trade -- Case studies; Iron industry and trade -- Case studies; Unemployment -- Case studies; Industrie -- Grands Lacs, Région des (Amérique du Nord); Industrie -- Allemagne -- Ruhr (Région); Industrie -- Pays de Galles (Sud); POLITICAL SCIENCE -- Public Policy -- Economic Policy; BUSINESS & ECONOMICS -- Government & Business; BUSINESS & ECONOMICS -- Development -- Economic Development; BUSINESS & ECONOMICS -- Development -- Business Development; BUSINESS & ECONOMICS -- Structural Adjustment; BUSINESS & ECONOMICS -- Development -- General; Industries; Iron industry and trade; Steel industry and trade; Unemployment; Germany -- Ruhr (Region); Great Lakes Region; South Wales; Industriepolitiek; Wederopbouw; Regionale ontwikkeling; Urban regions -- Economic conditions; Electronic books; Case studies; Case studies; Études de cas; Manchester (1992)